Autecology organisms, interactions and environmental dynamics - Walter, Gimme H.; Hengeveld, Rob (CRC Press/Taylor and Francis, 2014)
This book spells out the theoretical structure, methodology and philosophy of the science of autecology. The autecological approach focuses on the interactions of individual organisms (and their species-specific adaptations) with the spatio-temporal dynamics of their environment as a basis for interpreting patterns of diversity and abundance in natural systems. This organism-based approach to ecological interpretation provides a strong alternative to more traditional approaches and relates mechanistically to the underlying disciplines of anatomy, physiology, and behavior.
Keywords: Biotic communities.; Ecology -- Philosophy.; Paleoecology.; elektronické knihy; electronic books